Aspectos Silviculturais do "Pau-rosa" (Aniba Duckei Kostermans). II - Estudos sobre métodos de propagação - Vieira, Antonio Neto (Acta Amazonica, 1972)
The present paper deals with research carried out by the author at the Reserva Florestal Ducke (Ducke Forest Reserve), in Manaus, Amazonia. Brazil, on the propagation of "pau-rosa" (Aniba duckei Kostermans) beginning with cuttings, stump shoots, and transplants with and whithout leaves. Herein the author presents the incidence of sprouting, rooting and survival of cuttings, as well as other types of propagation employed in the field. Herein are presented the results of a comparative study based on the annual average height growth of the individuals over a period of two years. The results of this research appear in Tables II, III, IV, V, VI e VII.